The Effect of Concrete Mixture on Usage Fly Ash and Chicken Egg Shell Powder as Cement Substitutions in Concrete Compressive Strength - Farhan Fatahillah; Agung Sumarno (Neutron, 2022)
The purpose of this study was to determine the effect of utilizing fly ash and chicken egg shell powder on the compressive strength of concrete, workability, density and water absorption. In this study, testing was carried out with the use of fly ash waste and chicken egg shell powder with variations of 15% fly ash waste and variations of chicken egg shell powder by 10% and 17.5% at the age of 3 days, 7 days, 14 days, and 28 days. for the test objects used measuring with a diameter of 10 cm and a height of 20 cm as many as 36 test samples by making variations of the day as many as 3 samples of test objects. Concrete with a mixture of 15% Fly Ash waste and 10% Egg Shell Powder in test sample 2 obtained a compressive strength at the age of 28 days of 29.45 Mpa. Variation of the Normal Concrete sample got a compressive strength at the age of 28 days of 30.37 MPa. Variation of test sample 3 got a compressive strength at the age of 28 days of 21.16 Mpa.